Interaction between leprosy and HIV infection - Prima Sudarsa; Ratih Vibriyanti Karna; Luh Mas Rusyati (DiscoverSys Inc, 2018)
Introduction: Leprosy and Human Immunodeficiency Virus (HIV) infections still count as major health issues worldwide. Starting with the HIV pandemic back in the eighties, leprosy was feared to re-emerge as the HIV cases arose. Co-infections between leprosy and HIV were worried to cause an increase in leprosy cases, with worse clinical manifestation, predominantly toward the lepromatous spectrum, decrease in therapy response, and prolonged therapy period. Unlike its interaction with tuberculosis, HIV infection was turned out to not increasing nor deteriorating the manifestation of leprosy infection. All clinical spectrum of leprosy was found in HIV infection patients without predomination of lepromatous type. Responses to leprosy Multi-Drug Therapy (MDT) regimen were also found similar between leprosy patients with or without HIV.Conclusion: It is recommended to treat co-infective patients both with leprosy MDT and antiretroviral therapy. Manifestation of leprosy as a part of immune reconstitution syndrome need more attention and investigation.Keywords: HIV infection, leprosy, interaction